International Investment Law in African Courts - Mbengue, Makane Moïse; Schacherer, Stefanie (International Investment Law: An Analysis of Major Decisions, 2020)
This chapter identifies major categories of situations, events and institutions in which or through which questions of international investment law have been dealt with before African courts. The chapter is selective in nature and aims at showing tendencies instead of exhaustivity. A noteworthy tendency that becomes apparent through the chapter’s analysis is that the prevailing narrative of bypassing African courts and tribunals seems declining in importance as an increasing number of national investment law instruments foresee African judicial and arbitral institutions for the settlement of investment disputes.
Keywords: African national courts; Apartheid; EAC; ECOWAS; Investment arbitration; Land reform; National investment law; OHADA

Critical reflections on the development of integrated reporting: Are integrated reporting and IFRS competing frameworks? - Barker, R.; Teixeira, A. (The Routledge Handbook of Integrated Reporting, 2020)
Although integrated reporting emphasizes the contemporaneous relationship between financial and non-financial capitals, its primary purpose is to explain how an organization creates value over time. This is similar to the purpose of management commentary, which is part of a general-purpose financial report. We compare and contrast the information requirements of an integrated report with the type of information that supplements the primary financial information in general purpose financial reports, prepared in accordance with International Financial Reporting Standards (IFRS). We examine whether the information in those reports is intended to be forward-looking and predictive, whether non-financial capitals can (and should) be monetized in order to facilitate integration, and whether the reporting boundary should be drawn in different ways to serve different purposes. We find that the International Integrated Reporting Framework and IFRS do not serve different purposes or apply different approaches, but that – in essence – they are competing frameworks. While IFRS has highly developed standards for reporting financial capital, neither has a well-developed approach for reporting any other capital.

Les suites de l’accord amiable en afrique - Blanc, Gérard (L'accord amiable, 2020)